Residential Mobility of Older Adults in the Dutch Housing Market: Do Individual Characteristics and Housing Attributes Have an Effect on Mobility? - de Jong, Petra A.; Brouwer, Aleid E. (European Spatial Research and Policy, 2012)
The ageing of the population will change many societies in unprecedented ways. The changing age composition does not only create a burden on existing income systems and health care systems, but also affects the geographical mobility of populations. The objective of this paper is to provide some first insights into the moving behaviour of older adults in the Netherlands. By using data of the Housing Research Netherlands (HRN) 2009 survey, it was possible to investigate whether or not later-life residential mobility is influenced by individual characteristics and housing attributes. The responses of migrants and non-migrants are compared by conducting several two-way-chi-square analyses. The results of these descriptive analyses demonstrate that migrants indeed differ from non-migrants and that these differences are mostly related to housing attributes.